2009
DOI: 10.1002/bjs.6605
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life assessment after breast reconstruction

Abstract: Existing HRQL instruments are not sufficiently sensitive to detect clinically relevant problems following breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
3
32
0
4
Order By: Relevance
“…Si las mujeres consideran la apariencia física como aspecto muy importante en su vida, tendrán más alto nivel de estrés ante el CaMa (Baxter et al, 2006) y, como los instrumentos para detectar niveles de calidad de vida no siempre son sensibles a todos los aspectos (Potter, Thompson, Greenwood, Hopwood, & Winters, 2009), se debe evaluar la IC a través instrumentos específicos, a fin de detectar estas afectaciones que pueden ser desapercibidas por el equipo médico, y crear alternativas de intervención psicooncológica para mejorar la calidad de vida de las pacientes. Especialmente, se debe seguir investigando en las mujeres latinoamericanas aspectos relacionados con la sexualidad y las relaciones de pareja, dado que se reflejan aún tabúes sobre esta problemática.…”
Section: Alcances Y Limitaciones De La Revisiónunclassified
“…Si las mujeres consideran la apariencia física como aspecto muy importante en su vida, tendrán más alto nivel de estrés ante el CaMa (Baxter et al, 2006) y, como los instrumentos para detectar niveles de calidad de vida no siempre son sensibles a todos los aspectos (Potter, Thompson, Greenwood, Hopwood, & Winters, 2009), se debe evaluar la IC a través instrumentos específicos, a fin de detectar estas afectaciones que pueden ser desapercibidas por el equipo médico, y crear alternativas de intervención psicooncológica para mejorar la calidad de vida de las pacientes. Especialmente, se debe seguir investigando en las mujeres latinoamericanas aspectos relacionados con la sexualidad y las relaciones de pareja, dado que se reflejan aún tabúes sobre esta problemática.…”
Section: Alcances Y Limitaciones De La Revisiónunclassified
“…Although many studies investigated the psychosocial impact of BR after mastectomy, only few, mostly retrospective studies, focused on the effects of complications and subsequent surgery on psychological distress [10,13,14,15,16]. One retrospective quantitative study ( n = 60) covering a very short follow-up period of three months after surgery, reported that psychological distress levels were similar for women with and without complications [14].…”
Section: Introductionmentioning
confidence: 99%
“…One retrospective quantitative study ( n = 60) covering a very short follow-up period of three months after surgery, reported that psychological distress levels were similar for women with and without complications [14]. Two qualitative studies in very small samples ( n = 6, and n = 21) found that women were unprepared for the BR course, that they felt it was burdensome physically as well as emotionally, and that the additional operations and the long recovery period were disappointing and unexpected, regardless of complications [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, evidence suggests that women underestimate what their quality-of-life will be without reconstruction, and overestimate its benefits (Waljee, et al, 2011). In a systematic review of patient-reported outcomes after breast surgery, the majority of studies did not find significant differences in assessment of quality-of-life, or more specific measures of body image or sexuality/sexual functioning between women with mastectomy-alone or reconstruction (see Lee et al, 2009), although this research has been limited by the lack of valid and reliable breast surgery outcome measures (Pusic et al, 2007; Potter, Thomson, Greenwood, Hopwood, & Winters, 2009). Nonetheless, higher quality, prospective comparative studies such as Harcourt et al (2003) (included in Lee et al’s 2009 review), as well as Parker et al (2007), reveal similar patterns of adjustment across surgical groups, with adjustment in all groups improving over time.…”
Section: Introductionmentioning
confidence: 99%